Training to proficiency in surgery using simulation: is there a moral obligation?. Issue 1 (6th January 2022) - Toale, Conor; Morris, Marie; Kavanagh, Dara O
Abstract : A deontological approach to surgical ethics advocates that patients have the right to receive the best care that can be provided. The 'learning curve' in surgical skill is an observable and measurable phenomenon. Surgical training may therefore carry risk to patients. This can occur directly, through inadvertent harm, or indirectly through theatre inefficiency and associated costs. Trainee surgeon operating, however, is necessary from a utilitarian perspective, with potential risk balanced by the greater societal need to train future independent surgeons. New technology means that the surgical learning curve could take place, at least in part, outside of the operating theatre. Simulation-based deliberate practice could be used to obtain a predetermined level of proficiency in a safe environment, followed by simulation-based assessment of operative competence. Such an approach would require an overhaul of the current training paradigm and significant investment in simulator technology. This may increasingly be viewed as necessary in light of well-discussed pressures on surgical trainees and trainers. This article discusses the obligations to trainees, trainers and training bodies raised by simulation technology, and outlines the current arguments both against and in favour of a simulation-based training-to-proficiency model in surgery. The significant changes to the current training paradigm that would be required to implement such a model are also discussed.